DEFINITION PARAGRAPH : PROBLEM FACED BY STUDENTS - Impiani Zagoto; Restu Damai Laia; Senadaman Wau; M. Yunus Laia (Institut Pendidikan Tapanuli Selatan, 2022)
Definition paragraph is a paragraph which defines or explains something. In writing a definition paragraph, a writer should pay much attention to the organization and the language features of the paragraph. The third semester students of English Department of FKIP UNIRAYA, however, faced problems in writing the definition paragraph. This case motivated the writers to do a research to describe what the problems faced by the students are. This research was a kind of qualitative research. The result of the analysis showed that the students’ problems were in elaborating the controlling idea which is stated in topic sentences, and in drawing a concluding sentence. Moreover, the students have problems in grammar, spelling, punctuation, and mechanic in writing. Based on the result, it is concluded that the students are not able to write a good definition paragraph because of the problems faced. Hence, it is suggested that those students’ problems need to be considered in teaching the paragraph.